The trouble with twelfth grave [compact disc, unabridged] - Jones, Darynda (Jones, Darynda. Charley Davidson, 2017)
Ever since Reyes Farrow escaped from a hell dimension in which Charley Davidson accidentally trapped him, the son of Satan has been brimstone-bent on destroying the world his heavenly Brother created. His volatile tendencies have put Charley in a bit of a pickle. But that's not the only briny vegetable on her plate. While trying to domesticate the feral being that used to be her husband, she also has to deal with her everyday life of annoying all manner of beings, some corporeal, some not so much, as she struggles to right the wrongs of society. Only this time she's not uncovering a murder. This time she's covering one up.